SOMATOMETRICAL CHARACTERISTICS OF MALES 26–31 YEARS OLD WHO ARE ENGAGED IN HEALTHY FITNESS - Dolishnyi, M. V.; Mahlovanyy, A. V.; Rebrov, V. V. (Rehabilitation and Recreation, 2024)
Introduction. As is known in modern science, the human body can acquire representation in a different way, objectively tangential to its elements, such as microscopic and ultramicroscopic structures, as well as qualitative and quantitative characteristics. At the current stage, representatives of not only the Ukrainian, but also foreign scientific communities show unanimity in the view that in today’s conditions, one of the biggest problems of males of mature age is a significant decrease in the level of physical condition and health. The aim of the research is to determine the somatometric features of males aged 26–31. Methods of research: theoretical analysis and generalization of literature sources; anthropometry, pedagogical experiment, photography and posture analysis, methods of mathematical statistics. The results. As studied results of anthropometric measurements evidenced, most males (81.8%) have a body weight that corresponds to the norm, however, some males (18.2%) show a tendency to excess body weight. Accordingly, among males, the majority has an average and harmonious level of physical conditions (54.5%), but there are also fat individuals (45.5%). Thus, more than half of participants of the study (63.6%) were characterized by an acceptable ratio of waist and hips, but the rest fell into the zone of moderately high risk. Regarding the differences, males aged 29–31 years showed a general tendency to gain body weight, reflected in higher values of body mass index and Rohrer index, and excess waist and hip circumferences in the older group indicated accumulation of adipose tissue and a general increase in body volume. From this we can say that the differences between the groups of males aged 26–28 years and 29–31 years indicate a tendency to increase body weight and corresponding anthropometric indicators with age. Conclusions. The analysis of the data showed that there were significant differences between males aged 26–28 and males aged 29–31 according to most weight-height indicators of physical conditions (body weight, BMI, Rohrer index). Males aged 29–31 years had higher average values of body weight, BMI and Rohrer index compared to males aged 26–28 years, which indicated a tendency of increasing of body weight and increasing the respective indices with age. At the same time, the average body lengths in these age groups were similar and had no statistically significant differences.